In vivo imaging of bile accumulation and biliary infarction after common bile duct ligation in rats - Harnoß, Julian-Camill; Heidecke, C. D.; Vollmar, B.; Eipel, C. (European surgical research, 2011)
Obstructive cholestasis is caused by mechanical constriction or occlusion leading to reduced bile flow. Serious complications such as jaundice and even death may follow. Little is known about the initial phase of cholestasis and its consequences for the hepatic microarchitecture. This in vivo study aimed to characterize the nature and kinetics of developing obstructive cholestasis and focused on areas with biliary stasis and infarction by visualizing the autofluorescence of bile acids using intravital microscopy of the liver over a period of 30 h after bile duct ligation in rats. The innovation resided in performing fluorescence microscopy without applying fluorescent dyes. In animals subjected to obstructive cholestasis, the most significant changes observed in vivo were the concomitant appearance of (1) areas with bile accumulation increasing in size (6 h: 0.163 ± 0.043, 18 h: 0.180 ± 0.086, 30 h: 0.483 ± 0.176 mm2/field) and (2) areas with biliary infarction (6 h: 0.011 ± 0.006, 18 h: 0.010 ± 0.004, 30 h: 0.010 ± 0.050 mm2/field) as well as (3) a relation between the formation of hepatic lesions and enzyme activity in serum. The sequential in vivo analysis presented herein is a new method for the in vivo visualization of the very early changes in the hepatic parenchyma caused by obstructive cholestasis.
Gesehen am 03.08.2022